Development of Mold Flux for Heat‐Resistant Alloy Containing Al and Ti. Issue 2 (27th March 2015) - Yan, Wei; Chen, Weiqing; Yang, Yindong; Lippold, Carsten; McLean, Alex
Abstract : When continuous casting was used to replace electro‐slag remelting for the production of heat‐resistant alloy Incoloy 800 containing Al and Ti, there were a number of quality problems associated with the cast product which were attributed to the use of an inappropriate mold flux. The aim of the current investigation was to develop and evaluate an improved mold flux by combining data derived from laboratory experiments with results obtained from plant‐trials. The effects of composition on viscosity and heat transfer properties were investigated and a new mold flux was designed with improved casting behavior. By decreasing the characteristic melting temperatures, selecting an appropriate viscosity and enhancing the heat transfer properties, slab quality was improved. Chemical analysis combined with X‐ray diffraction (XRD) and scanning electron microscopy (SEM) evaluation of liquid flux and flux film samples indicated that changes in composition, characteristic temperatures, and viscosity during the casting operation were negligibly small. The flux film with a thickness of 1.1 mm, a crystalline ratio of 30%, and cuspidine as the main crystalline phase was beneficial for improving heat transfer thus strengthening the initial shell and improving the quality of the cast product. Abstract : Integrated studies from theoretical analysis, laboratory experiments and field trial are conducted to optimize the mold flux for heat‐resistant alloy containing Al and Ti. The results present modified mold flux with reduced melting temperature, good lubrication, and low crystalline fraction, promotes heat transfer which enhances thickening and strengthening of the initial shell, all of which contribute to improved slab quality.